The relationship between emotional intelligence and psychological well-being of teachers in the district of Petaling Perdana / Nur Baizura Mohd Yusof - Mohd Yusof, Nur Baizura (2015)
Teachers who experience low level of psychological well-being unintentionally demonstrate negative work behaviors such as abusing sick leave and often come late to work, resulting in difficulty to lift the quality of education. Thus, it is important to identify the factors that could enhance teachers' psychological well-being within the school compound. The purpose of this study was to examine the relationship between emotional intelligence and psychological well-being among teachers. 100 daily secondary school teachers in the district of Petaling Perdana completed the surveys for this study. They were selected based on simple random sampling. Data were collected using a descriptive method and the questionnaire was used as an instrument. Based on the data collected, the findings showed that generally daily secondary school teachers in the Petaling Perdana district have high level of psychological wellbeing, high level of emotional intelligence and there is no relationship between psychological well-being and emotional intelligence. In this study, it was found that teachers of district Petaling Perdana perceived high level of emotional intelligence and psychological well-being which indicated that they were stable emotionally and psychologically. However, the findings also revealed that there was a negative and weak relationship between emotional intelligence and psychological well-being. This highlighted that psychological well-being of the teachers were not influenced by emotional intelligence. It shows that there could be other factors that influenced psychological well-being of the teachers. Besides that, the findings of this study are believed to have implications to the role of principal in sustaining good leadership among teachers. Based on the findings too, this study also provides recommendations for practices and future research.